2008
DOI: 10.1002/anie.200801009
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Intermolecular Aerobic Oxidative Amination of Terminal Alkenes: Efficient Synthesis of Linear Allylamine Derivatives

Abstract: Dedicated to Professor Xiyan Lu on the occasion of his 80th birthdayThe rich variety of nitrogen-containing molecules that occur as natural and synthetic products has inspired considerable interest in the development of new methods for their syntheses.[1] Among the strategies involving the direct amination of olefins by CÀN bond formation, [2][3] the synthesis of amine derivatives by intermolecular dioxygen-coupled oxidative amination of olefins is particularly attractive. [4][5][6] Palladium-catalyzed methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…10 Liu and coworkers achieved aerobic allylic imidation under similar conditions by employing 40 mol % of maleic anhydride as an additive in the reaction (eq 2). 11 Finally, we reported that use of 4,5-diazafluorenone as an ancillary ligand enables aerobic allylic acetoxylation of alkenes under 1 atm O 2 (eq 3). 12 …”
Section: Introductionmentioning
confidence: 99%
“…10 Liu and coworkers achieved aerobic allylic imidation under similar conditions by employing 40 mol % of maleic anhydride as an additive in the reaction (eq 2). 11 Finally, we reported that use of 4,5-diazafluorenone as an ancillary ligand enables aerobic allylic acetoxylation of alkenes under 1 atm O 2 (eq 3). 12 …”
Section: Introductionmentioning
confidence: 99%
“…O 2 or air). 12,13 Significant amounts of double bond isomerization in both the starting materials and products (up to 50%) necessitate the use of large excesses of olefin and limit applications in fine chemical synthesis. 1214 …”
Section: Design Principlesmentioning
confidence: 99%
“…It is significant to note that these preparative conditions contrast those of previously reported aerobic allylic C—H amination methods ( vida supra ). 12,13 …”
Section: Reaction Scopementioning
confidence: 99%
“…This assumption is supported by the presence of one band at 350 cm -1 in the infrared spectrum, assigned to the stretching frequency of the Pd-Cl bond, which is characteristic of a trans dichloride isomer. 40 Considering that a variety of palladium(II) complexes have been successfully studied as catalysts in oxidative amination of alkenes reactions, [25][26][27][28][29][30][31][32][33][34][35][36][37] we tested the behavior of complexes 2 and 3 in the reaction of phthalimide with allyl butyl ether.…”
Section: Scheme 1 Synthesis Of 35-bis(benzotriazol-1-ylmethyl)toluementioning
confidence: 99%
“…24 On the other hand, a variety of palladium(II) complexes have been successfully studied as catalysts for the aerobic oxidative amination of unactivated alkenes to yield amine derivatives. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] This catalytic reaction leads to the formation of imines or enamines, via b-hydride elimination, through a mechanism analogous to the well-known Wacker process. 25 In this communication we report the synthesis and characterization of the new ligand 3,5-bis(benzotriazol-1-ylmethyl)toluene (1) …”
Section: Introductionmentioning
confidence: 99%